Psychological readiness to return to sport following injury: a state-of-the-art review - Podloga, L.; Wadey, R.; Caron, J.; Fraser, J. J.; Ivarsson, A.; Heil, J.; Podlog, S.; Casucci, T. (International Review of Sport and Exercise Psychology, 2022)
Psychological readiness to return to sport (RTS) after injury is a critical and timely area of research that has received significant research attention of late. Although research on psychological readiness to RTS has burgeoned in recent years, there remains a lack of conceptual clarity on what psychological readiness is. As such, our aims in this review of the state of the art (consistent with the typology of Grant and Booth) are threefold. First, we articulate key conceptual issues and questions regarding the nature of psychological readiness and offer a preliminary nomothetic definition of the construct. Based on the definition, we advance several hypotheses for testing in future research. Second, we discuss research examining correlates of psychological readiness and, third, we look at empirical work focused on outcomes of psychological readiness. Our review draws upon literature spanning various disciplines and cultures/languages.